Wizerunek Konga Belgijskiego w piśmiennictwie polskim i niderlandzkojęzycznym - Czarnecka, Bożena (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The text corpus used for the presentation of the image of the Belgian Congo in the book "Image of the Belgian Congo in Polish and Netherlandic Literature" is heterogeneous. Separate works most often can not be clearly classified. They are most often classified into popular-science, travel literature, fiction, report, memories, correspondence, adventure novel, children’s literature or the comic book. Diversity of the analysed texts needed a remarkably wide and interdisciplinary approach. The uniform methodological work model could not be applied in the analysis of the particular texts.Therefore, the conducted research activities were based on the cultural and postcolonial studies.A pluralistic reflection of this kind allowed the interpretation of possible cultural references in the analysed literary texts and the interaction of different cultural texts, representing the so called high culture as well as the low culture. Such an approach allowed the analysis of certain components of the image and the indication of a transformation direction. It is worth emphasizing that identifying of the components of the image of Congo turned out to be of arbitrary nature to a great extent and as a methodological intention it was to clarify the presentation of research results, which would resultin finding a common denominator for the texts of different origin, representing different traditions. Each of the texts analysed in the book (belonging to the so called belles lettres or to non-fi ction) was treated as a phenomenon marked ideologically and evaluative and not as a neutral and objectiver eflection of reality. The book is not aspiring to be a historical and sociological overview of the image of Congo in the Flemish (Belgian) and Polish society — it focuses on the analysis of the written, set on paper, image of that country. Such an approach is connected with the definition of the image applied for the needs of this book.
Keywords: literatura flamandzka -- tematy, motywy; relacje z podróży polskie -- historia i krytyka; demokratyczna Republika Konga -- historia; demokratyczna Republika Konga -- w wyobrażeniach społecznych; demokratyczna Republika Konga -- w literaturze